Time to move towards opt-out testing for HIV in the UK. Issue 7608 (28th June 2007) - Hamill, M; Burgoine, K; Farrell, F; Hemelaar, J; Patel, G; Welchew, D E; Jaffe, H W
Abstract : M Hamill and colleagues believe the UK could do more to ensure people know their HIV status